Gamma irradiation-induced genetic variability and its effects on the phenotypic and agronomic traits of groundnut (Arachis hypogaeaL.) - Saibari, Imane; Barrijal, Saïd; Mouhib, Mohammed; Belkadi, Najlae; Hamim, Ahlam (Frontiers in Genetics, 2023)
In order to increase genetic variability for the improvement of groundnut, two varieties Kp29 and Fleur 11were treated with six gamma irradiation doses. A significant effect of mutagenesis ex-presses itself distinctly in the stem lengths, roots, and survival percentage observed in both varie-ties. Thus the radio-sensitivity test showed an LD50 of 436.51Gy for Kp29 and 501.18 Gy for Fleur11. Furthermore, this study revealed putative mutants with variable agro-morphologic traits. Seven chlorophyll mutants and various shape and color seeds mutants were obtained. This study proved the potency of gamma irradiation to induce high genetic variability led to the emergence of certain mutations of economic importance.